Strengthening the Understanding of Church Law and the Spirituality of Consecrated Life as a Means of Fostering the Faith of the People in Realizing Salvation (SALUS ANIMARUM) - Asrot Purba (Abdimas Paspama, 2023)
The low understanding of the Church Law, the Catechism of the Catholic Church, and the spirituality of consecrated life can limit the ability of the people to live the faith in its entirety. This Community Service activity aims to increase the understanding of the people about the pastoral functions of the Church Law, strengthen Christian spirituality, and encourage participation in church life with an orientation to the salvation of the soul (salus animarum). The program is implemented through an educational-participatory approach that includes interactive lectures, group discussions, pastoral case studies, faith reflection, simulation, and mentoring. Evaluation was carried out using pre-test and post-test, activeness observation, reflection sheets, satisfaction questionnaires, and assessments of participants' follow-up plans. The draft results showed an increase in the average score of participants from 57.5 to 86.8 in four aspects, namely understanding of Church Law, understanding the Catechism, spirituality of consecrated life, and pastoral participation. Participants also produce faith reflections, pastoral action plans, and commitments to apply the values of the Church in family and community life. The discussion shows that the Law of the Church is easier to understand when it is placed as a pastoral instrument and linked to the concrete experience of the people. The sustainability of the program is directed through the formation of faith building groups, the use of modules, and periodic mentoring by congregational cadres and pastoral partners.